The Competent Public Sphere - Roberts, J. author. aut Link
VI, 204 p.
Keywords: Suggesting that an expressive ideology has arisen within the workplace public sphere around the theme of 'competence', this book explores the hegemony of global finance and the fetishism of the new economy, exposing the dilemmas of the competence agenda, and illustrating how competence is played out in the workplace public sphere.